Smell the Label: Odors Influence Label Perception and Their Neural Processing - Schicker, Doris; Khorisantono, Putu A.; Dervishi, Qëndresa Rramani; Lim, Shirley X.L.; Saruco, Elodie; Pleger, Burkhard; Schultz, Johannes; Ohla, Kathrin; Freiherr, Jessica (Journal of Neuroscience, 2025)
Providing nutrition or health labels on product packaging can be an effective strategy to promote a conscious and healthier diet. However, such labels also have the potential to be counterproductive by creating obstructive expectations about the flavor of the food and influencing odor perception. Conversely, olfaction could significantly influence label perception, whereby negative expectations could be mitigated by pleasant odors. This study explored the neural processing of the interplay between odors and nutrition labels using fMRI in 63 participants of either sex, to whom we presented beverage labels with different nutrition-related statements either with or without a congruent odor. On a behavioral level, the products for which the label was presented together with the odor were in general perceived as more positive than the same labels without an odor. Neuroimaging results revealed that added odors significantly altered activity in brain regions associated with flavor and label processing as well as decision-making, with higher activations in the right amygdala/piriform cortex (Amy/pirC) and orbitofrontal cortex. The presentation of odors induced pattern-based encoding in the right dorsolateral prefrontal cortex, the left ventral striatum/nucleus accumbens, and the right Amy/pirC when accounting for behavioral differences. This suggests that odors influence the effects of labels both on a neural and behavioral level and may offer the possibility of compensating for obstructive associations. The detailed mechanisms of odor and statement interactions within the relevant brain areas should be further investigated, especially for labels that evoke negative expectations.
CRIS-Team Scopus Importer:2025-04-18
Keywords: fMRI; food; label; nutrition; odor; olfaction